Water-based composite adhesive and application thereof
A water-based composite adhesive with ketone hydrazine cross-linking improves substrate adhesion and heat resistance, addressing wrinkling and blistering issues in gold and silver cardboard during high-temperature processes.
Patent Information
- Application Number
- CN202411269263.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional gold and silver cardboard used in packaging is prone to wrinkling and blistering during high-temperature processes such as hot pressing and hot shock embossing due to differences in thermal expansion coefficients and low glass transition temperatures of the materials, leading to misalignment and deformation.
A water-based composite adhesive comprising specific monomers, surfactants, and initiators that form a stable hydrazone bond through ketone hydrazine cross-linking, enhancing substrate adhesion and heat resistance, preventing softening and misalignment under high temperatures.
The adhesive maintains substrate alignment and prevents blistering and wrinkling during high-temperature processes, ensuring the gold and silver cardboard remains flat and stable.
Smart Images

Figure CN119193051A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glue production, and in particular to a water-based composite glue and application thereof. Background Art
[0002] Gold and silver cardboard is made of laser film and white cardboard or powder-gray cardboard bonded by composite glue. It is mainly used for packaging products with waterproof requirements such as cigarette packages, wine packages, electronic components, and cosmetics.
[0003] Composite glue is a special glue for gold and silver cardboard. With the rapid development of packaging products and the improvement of process requirements, traditional gold and silver cardboard cannot be used for high-temperature processes such as hot pressing and hot shock embossing. This is because under high-temperature processes such as hot pressing and hot shock embossing, traditional gold and silver cardboard is prone to wrinkling and blistering. Summary of the invention
[0004] The main purpose of the present invention is to provide a water-based composite adhesive and its application, aiming to solve the problem in the prior art that gold and silver cardboard is prone to wrinkling and bubbling under high-temperature processes such as hot pressing.
[0005] To achieve the above object, the present invention provides a water-based composite adhesive, comprising the following raw material components in parts by weight:
[0006] 0.5 to 1.2 parts of a first cross-linking monomer, wherein the first cross-linking monomer comprises an propylene compound having a ketocarbonyl group;
[0007] 0.25 to 0.6 parts of a second crosslinking monomer, wherein the second crosslinking monomer comprises an alkyl compound having at least two hydrazide groups;
[0008] 1.1 to 2.8 parts of surfactant;
[0009] 30 to 45 parts of acrylic acid ester having a glass transition temperature of -70 to 60°C;
[0010] 1-2 parts of acrylic acid;
[0011] 5 to 10 parts of acrylic acid ester with a glass transition temperature of 106 to 158°C;
[0012] 0.3-0.5 parts of initiator;
[0013] 35-45 parts of water.
[0014] In one embodiment, the following raw material components are further included in parts by weight: 0.01 to 0.03 parts of acrylic acid ester.
[0015] In one embodiment, the acrylic alcohol ester includes at least one of ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diethylene glycol dimethacrylate.
[0016] In one embodiment, the following raw material components are further included in parts by weight: 0.1 to 0.3 parts of a buffer; and 0.1 to 0.5 parts of a molecular weight regulator.
[0017] In one embodiment, the first cross-linking monomer comprises diacetone acrylamide, ethyl acetoacetate methacrylate or N,N-methylenebisacrylamide; and / or,
[0018] The second cross-linking monomer includes adipic acid dihydrazide, oxalic acid dihydrazide or succinic acid dihydrazide.
[0019] In one embodiment, the acrylic acid ester having a glass transition temperature of -70 to 60° C. comprises at least one of ethyl acrylate, butyl acrylate and isooctyl acrylate; and / or,
[0020] The acrylic acid ester having a glass transition temperature of 106 to 158° C. includes at least one of isobutyl methacrylate, isooctyl methacrylate or butyl methacrylate.
[0021] In one embodiment, the initiator comprises ammonium persulfate, potassium persulfate or sodium persulfate; and / or,
[0022] The surfactant includes anionic surfactant and nonionic surfactant. The anionic surfactant includes sulfate, sulfonate or sodium sulfate of fatty alcohol ether. The nonionic surfactant includes ethanolamide, alkylphenol polyoxyethylene ether or fatty alcohol polyoxyethylene.
[0023] The present invention also provides an application of the above-mentioned water-based composite adhesive in the production of gold and silver cardboard.
[0024] In one embodiment, the steps include:
[0025] S10, applying water-based composite adhesive to one side of the laser film, laminating it with one side of the white cardboard or the powder-gray cardboard, and laminating them with a hot roller to obtain a composite material;
[0026] S20, performing hot embossing on the other side of the laser film in the composite to obtain gold and silver card paper.
[0027] In one embodiment, in step S10, the laser film comprises an aluminized polypropylene film or an aluminized polyester film; and / or,
[0028] In step S20, the temperature of the hot pressing is 110-130° C.; and / or,
[0029] In step S20, the heat pressing time is 5 to 10 seconds.
[0030] The present invention provides a water-based composite adhesive and its application. After the water-based composite adhesive is coated on a substrate, as the water in the water-based composite adhesive evaporates during the drying process, the latex particles in the water-based composite adhesive gradually move closer together, and the first monomer and the second monomer in the latex particles react with ketone hydrazine to form a stable hydrazone bond to construct a cross-linked network, that is, the ketone carbonyl group in the propylene compound having a ketone carbonyl group and the hydrazide group in the alkyl compound having at least two hydrazide groups react with ketone hydrazine. Since the second monomer has at least two hydrazide groups, it can react with multiple first monomers, and the second monomer can also react with the second monomer to form a hydrazone bond. The product generated by ketone hydrazine cross-linking forms a wet adhesion on a substrate with weak surface polarity (such as an aluminum-plated laser film), enhances the positioning relationship between the substrates, and at the same time improves the glass transition temperature and heat resistance of the glue, preventing the glue in the product from softening or even flowing under high-temperature processes such as hot pressing, so that the substrates are misaligned with each other, resulting in blistering on the surface of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0032] Figure 1 This is an appearance diagram of a gold and silver card prepared by using the method of Example 4 using the water-based composite adhesive in Example 1 provided by the present invention;
[0033] Figure 2 This is an appearance diagram of a gold and silver card prepared by using the method of Example 4 using the water-based composite adhesive in Comparative Example 1 provided by the present invention.
[0034] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0035] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0036] Gold and silver cardboard is made of laser film and white cardboard or powder-gray cardboard bonded by composite glue. It is mainly used for packaging products with waterproof requirements such as cigarette packages, wine packages, electronic components, and cosmetics.
[0037] Composite glue is a special glue for gold and silver cardboard. With the rapid development of packaging products and the improvement of process requirements, traditional gold and silver cardboard cannot be used for high-temperature processes such as hot pressing and hot shock embossing. This is because under high-temperature processes such as hot pressing and hot shock embossing, traditional gold and silver cardboard is prone to wrinkling and blistering.
[0038] This wrinkling and blistering phenomenon is mainly due to the fact that the laser film is a thermoplastic material, while the cardboard is a porous fiber material. Under conditions above 60°C, the thermal expansion coefficients of the laser film and the cardboard are different, resulting in deformation of the gold and silver cardboard. At the same time, the traditional composite adhesive has a low glass transition temperature and is easy to soften or even flow under high-temperature process conditions such as hot pressing, which will also aggravate the relative displacement between the laser film and the cardboard in the gold and silver paper.
[0039] To sum up, the current technical defects of laser film composite adhesive are: not heat-resistant, the glue cannot be positioned, and the glue strength decreases at temperatures above 60°C.
[0040] In view of this, the present invention provides a water-based composite adhesive, comprising the following raw material components in parts by weight: 0.5 to 1.2 parts of a first cross-linking monomer, wherein the first cross-linking monomer comprises an acrylic compound having a ketone carbonyl group; 0.25 to 0.6 parts of a second cross-linking monomer, wherein the second cross-linking monomer comprises an alkyl compound having at least two hydrazide groups; 1.1 to 2.8 parts of a surfactant; 30 to 45 parts of an acrylate having a glass transition temperature of -70 to 60°C; 1 to 2 parts of acrylic acid; 5 to 10 parts of an acrylate having a glass transition temperature of 106 to 158°C; 0.3 to 0.5 parts of an initiator; and 35 to 45 parts of water.
[0041] In the technical scheme of the present invention, after the water-based composite adhesive is coated on the substrate, as the water in the water-based composite adhesive evaporates during the drying process, the latex particles in the water-based composite adhesive gradually move closer, and the first monomer and the second monomer in the latex particles react with ketone hydrazine to form a stable hydrazone bond to construct a cross-linked network, that is, the ketone carbonyl in the propylene compound having a ketone carbonyl group and the hydrazide group in the alkyl compound having at least two hydrazide groups react with ketone hydrazine. Since the second monomer has at least two hydrazide groups, it can react with multiple first monomers, and the second monomer can also react with the second monomer to form a hydrazone bond. The product generated by ketone hydrazine cross-linking forms a wet adhesion on a substrate with weak surface polarity (such as an aluminum-plated laser film), enhances the positioning relationship between the substrates, and at the same time improves the glass transition temperature and heat resistance of the glue, preventing the glue in the product from softening or even flowing under high-temperature processes such as hot pressing, so that the substrates are misaligned with each other, resulting in blistering on the surface of the product.
[0042] Among them, the mass fraction of surfactant in the range of 1.1 to 2.8 parts can ensure that the surface tension of the water-based composite adhesive system is low, help the emulsion to disperse evenly, and promote the spreading of emulsion particles on the surface of the substrate when applied. Acrylate is part of the main body of the adhesive. Acrylate monomers are connected to each other through free radical polymerization to form linear or branched macromolecular polymers. These macromolecular polymers provide basic adhesion and cohesion in the composite adhesive. Acrylate with a glass transition temperature of -70 to 60°C in the range of 30 to 45 parts and acrylate with a glass transition temperature of 106 to 158°C in the range of 5 to 10 parts can ensure that the glass transition temperature of the water-based composite adhesive is low, so that good adhesion can be maintained at a lower temperature, and materials can be effectively bonded at low temperatures. The mass fraction of acrylic acid in the range of 1 to 2 parts increases the interaction between polymer chains, thereby affecting the adhesion, cohesion and durability of the adhesive. The mass fraction of initiator in the range of 0.3 to 0.5 parts can better start the polymerization reaction and control the polymerization rate and molecular weight. Water is the solvent for the above ingredients, and its mass fraction is in the range of 35 to 45 parts. 1) It can better control the polymerization reaction of the main monomer acrylate and acrylic acid during the emulsion production process, 2) It can also inhibit the ketone hydrazine reaction of the first monomer and the second monomer during the storage of the emulsion, 3) It is also easy to coat and use the composite latex, and 4) It is more convenient for the rapid evaporation of water under heat treatment, the first monomer and the second monomer in the emulsion particles to approach each other more quickly and finally form a continuous film.
[0043] In some embodiments of the present invention, the following raw material components are also included in mass fractions: 0.01 to 0.03 parts of acrylate. The acrylate groups in the acrylate can undergo polymerization reaction with the polymer chains in the water-based composite adhesive (including the polymer chains formed by the polymerization of the main monomer acrylate and the polymer chains formed by the first monomer and the second monomer through the ketone hydrazine reaction) to form cross-linking points, thereby enhancing the cross-linking density, making the polymer more densely distributed on the substrate, enhancing the contact points between the polymer and the substrate, and further enhancing the adhesion between the polymer and the substrate. At the same time, the increase in the cross-linking density of the polymer allows the emulsion to form a more continuous and dense film during the film-forming process, thereby improving the thermal stability and chemical stability of the film. Therefore, the mass fraction of acrylate within the above range can ensure the stability of the composite material in processes such as hot pressing and thermal shock convexo ...
[0044] In some embodiments of the present invention, the acrylic alcohol ester includes at least one of ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diethylene glycol dimethacrylate. That is, the acrylic alcohol ester can be any one of ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diethylene glycol dimethacrylate, or two or three of ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diethylene glycol dimethacrylate, all of which are within the protection scope of the present invention. The above acrylic alcohol esters can provide two acrylate groups to ensure the mechanical stability of the glue. If there are too many acrylate groups, the glue will have poor water resistance after drying and forming a film.
[0045] In some embodiments of the present invention, the following raw material components are also included in mass fractions: 0.1 to 0.3 parts of a buffer; 0.1 to 0.5 parts of a molecular weight regulator. The buffer includes sodium bicarbonate, ammonium bicarbonate or sodium acetate. The mass fraction of the buffer in the range of 0.1 to 0.3 parts can better control the pH value of the polymerization system during the emulsion production process to ensure that the polymerization reaction proceeds smoothly; the molecular weight regulator includes n-dodecyl mercaptan or tris-thiol propionate diethylhexyl. The mass fraction of the molecular weight regulator in the range of 0.1 to 0.5 parts can effectively control the average molecular weight of the polymer to avoid excessively high or low molecular weight.
[0046] In some embodiments of the present invention, the first crosslinking monomer includes diacetone acrylamide, ethyl acetoacetate methacrylate or N,N-methylenebisacrylamide. The first crosslinking monomer can provide more ketone carbonyl groups, promote the ketone hydrazine crosslinking reaction, ensure more wetting and adhesion on the substrate, enhance the heat resistance of the glue and the positioning relationship between the substrates, prevent the substrates from being misaligned due to the large difference in thermal expansion coefficients of different substrates under high temperature processes, and further prevent the softening of the glue from exacerbating the misalignment of the substrates and causing wrinkling and blistering.
[0047] In some embodiments of the present invention, the second crosslinking monomer includes adipic acid dihydrazide, oxalic acid dihydrazide or succinic acid dihydrazide. The above second crosslinking monomer can provide more hydrazide groups, promote ketone hydrazide crosslinking reaction, ensure more wetting and adhesion on the substrate, enhance the heat resistance of the glue and the positioning relationship between the substrates, prevent the substrates from being misaligned due to the large difference in thermal expansion coefficients of different substrates under high temperature processes, and further prevent the softening of the glue from exacerbating the misalignment of the substrates and causing wrinkling and blistering.
[0048] In some embodiments of the present invention, the acrylic acid ester with a glass transition temperature of -70 to 60°C includes at least one of ethyl acrylate, butyl acrylate, and isooctyl acrylate. That is, the acrylic acid ester with a glass transition temperature of -70 to 60°C can be any one of ethyl acrylate, butyl acrylate, and isooctyl acrylate, or two or three of ethyl acrylate, butyl acrylate, and isooctyl acrylate, all of which are within the protection scope of the present invention. Selecting the above acrylic acid esters can ensure better adhesion and flexibility of the glue.
[0049] In some embodiments of the present invention, the acrylic acid ester having a glass transition temperature of 106-158°C includes at least one of isobutyl methacrylate, isooctyl methacrylate or butyl methacrylate. That is, the acrylic acid ester having a glass transition temperature of 106-158°C may be any one of isobutyl methacrylate, isooctyl methacrylate or butyl methacrylate, or may be two or three of isobutyl methacrylate, isooctyl methacrylate or butyl methacrylate, all of which are within the protection scope of the present invention. Selecting the above acrylic acid esters can ensure that the glue has good adhesion and heat resistance to film materials such as laser films.
[0050] In some embodiments of the present invention, the initiator includes ammonium persulfate, potassium persulfate or sodium persulfate. By selecting the above initiator, free radicals or other active centers can be generated quickly, which can react with monomer molecules, thereby initiating a chain reaction, and a four-stage reaction process of chain initiation, chain transfer, chain growth, and chain termination occurs, and the monomer is finally converted into a high molecular polymer to form a self-crosslinking emulsion. The monomer molecules include: a main monomer (acrylate with a glass transition temperature of -70 to 60°C), a polar monomer (acrylic acid) and an auxiliary monomer (5 to 10 parts of acrylate with a glass transition temperature of 106 to 158°C). Preferably, the initiator is ammonium persulfate. The free radicals or other active centers provided by the initiator play a role not only in the synthesis process of the water-based composite glue, but also in the film formation of the glue, that is, providing free radicals or other active centers for the ketohydrazine reaction, promoting the rapid progress of the ketohydrazine reaction.
[0051] In some embodiments of the present invention, the surfactant includes an anionic surfactant and a nonionic surfactant, and the anionic surfactant includes sulfate, sulfonate or sodium sulfate of fatty alcohol ether, wherein sulfate includes sodium dodecyl sulfate or sodium hexadecyl sulfate, sulfonate includes sodium dodecylbenzene sulfonate or alkylnaphthalene sulfonate, and sodium sulfate of fatty alcohol ether includes sodium dodecyl alcohol ether sulfate. The nonionic surfactant includes ethanolamide, alkylphenol polyoxyethylene ether or fatty alcohol polyoxyethylene ether, wherein ethanolamide includes coconut oil diethanolamide or coconut oil monoethanolamide, alkylphenol polyoxyethylene ether includes nonylphenol polyoxyethylene ether (OP-10) or octylphenol polyoxyethylene ether, and the carbon chain length of fatty alcohol in fatty alcohol polyoxyethylene ether ranges from C12 to C18.
[0052] Among them, when water is used as the solvent, the surfactant is mainly anionic surfactant and supplemented by non-ionic surfactant, which can better promote the dispersion and stabilization of polymers in the water-based composite adhesive, prevent flocculation and precipitation, and significantly reduce the surface tension of water, so that the water-based composite adhesive can be easily spread on the surface of the substrate.
[0053] The present invention also provides an application of the aforementioned water-based composite adhesive in the production of gold and silver cardboard. The application includes the aforementioned water-based composite adhesive and has all the technical effects of the aforementioned water-based composite adhesive, which will not be described in detail here.
[0054] In some embodiments of the present invention, the following steps are included:
[0055] S10, applying water-based composite adhesive to one side of the laser film, laminating it with one side of the white cardboard or the powder-gray cardboard, and laminating them with a hot roller to obtain a composite material;
[0056] S20, performing hot embossing on the other side of the laser film in the composite to obtain gold and silver card paper.
[0057] In the technical scheme of the present invention, the water-based composite adhesive can be synthesized by the synthesis process of the normal pressure acrylic emulsion, and the first monomer and the second monomer in the obtained water-based composite adhesive will not undergo a ketone-hydrazine reaction for cross-linking. This is because there is water in the system, and the reaction between the ketone carbonyl group and the hydrazine part (-NHNH2) of the hydrazide group (-CONH-NH2) is usually carried out by a nucleophilic addition reaction, and the presence of water inhibits the ketone-hydrazine reaction. In step S10, when the water-based composite adhesive is applied to one side of the laser film and attached to one side of the white cardboard or the powder gray cardboard, and the composite is performed by the hot roller process, the water content of the glue evaporates rapidly due to the high temperature of the hot roller (usually 100-120°C), thereby forming a film between the laser film and the cardboard; wherein, as the water content in the glue emulsion on the laser film and the cardboard evaporates at an instantaneous high temperature, the first monomer and the second monomer in the emulsion particles between the laser film and the cardboard undergo a ketone-hydrazine cross-linking reaction to form a stable hydrazone bond, and the formed hydrazone bond constructs a more stable cross-linking network. In addition, the product generated by ketone hydrazine cross-linking forms a wet adhesion on the aluminum-plated film with weak surface polarity, strengthens the positioning relationship between the film and the cardboard, and prevents blistering during hot pressing on the aluminum-plated film surface.
[0058] In some embodiments of the present invention, in step S10, the laser film includes an aluminized polypropylene film or an aluminized polyester film. The laser film can be a polypropylene film (OPP film) or a polyester film (PET film) formed by hollow aluminizing technology. The surface polarity of the laser film is weak, and the water-based composite adhesive of the present invention can be used for better adhesion.
[0059] In some embodiments of the present invention, in step S20, the temperature of the hot pressing is 110-130° C. The temperature of the hot pressing within the above range can ensure that the surface of the aluminized film can be printed with patterns quickly, while avoiding misalignment between the aluminized film and the cardboard, and preventing the softening of the glue, so that the gold and silver cardboard is relatively flat without wrinkles and bubbles.
[0060] In some embodiments of the present invention, in step S20, the heat pressing time is 5 to 10 seconds. The heat pressing time within the above range can ensure that the pattern can be printed on the surface of the aluminized film well, while avoiding misalignment between the aluminized film and the cardboard, and preventing the softening of the glue, so that the gold and silver cardboard is relatively flat without wrinkles and bubbles.
[0061] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0062] Example 1
[0063] A water-based composite adhesive comprises the following raw material components in parts by weight:
[0064] 1g of diacetone acrylamide; 0.4g of adipic acid dihydrazide; 1g of sodium lauryl sulfate; 1.4g of OP-10; 20g of butyl acrylate; 17g of isooctyl acrylate; 1.5g of acrylic acid; 7g of isobutyl methacrylate; 0.02g of ethylene glycol dimethacrylate; 0.4g of ammonium persulfate; 40g of water; 0.3g of n-dodecyl mercaptan; and 0.2g of sodium bicarbonate.
[0065] The preparation method of the water-based composite adhesive is as follows: in a synthesis device equipped with a constant temperature water bath, a cantilever stirring disperser, a 1000 mL four-necked flask, a serpentine condenser, a constant pressure funnel and a thermometer, firstly, 20 g of water, 0.2 g of sodium bicarbonate and 0.7 g of OP-10 are added to the four-necked flask, the temperature is raised to 85° C., 0.4 g of ammonium persulfate is added, the reaction is carried out for 4 minutes, and the emulsified monomer (i.e., 1 g of sodium dodecyl sulfate, OP-10) is added dropwise for 4 hours. 0.7g, water 20g, acrylic acid 1.5g, butyl acrylate 20g, isooctyl acrylate 17g, isobutyl methacrylate 7g, ethylene glycol dimethacrylate 0.02g, n-dodecyl mercaptan 0.3g), after the emulsified monomers are added, keep the temperature constant for 90 minutes, raise the internal temperature to 90°C, keep warm for one hour, lower the internal temperature below 40°C, add 1.2g ammonia water, adjust the pH value to 6, add 0.4g adipic acid dihydrazide, add mineral oil defoamer and stir for 30 minutes, filter with 300 mesh nylon cloth to obtain a water-based composite adhesive.
[0066] Example 2
[0067] A water-based composite adhesive comprises the following raw material components in parts by weight:
[0068] 0.5 g of diacetone acrylamide; 0.25 parts of adipic acid dihydrazide; 0.5 g of sodium lauryl sulfate; 1.1 g of OP-10; 15 g of butyl acrylate; 15 g of isooctyl acrylate; 1 g of acrylic acid; 5 g of isobutyl methacrylate; 0.01 g of ethylene glycol dimethacrylate; 0.3 g of ammonium persulfate; 35 g of water; 0.1 g of n-dodecyl mercaptan; and 0.1 g of sodium bicarbonate.
[0069] Example 3
[0070] A water-based composite adhesive comprises the following raw material components in parts by weight:
[0071] 1.2g of diacetone acrylamide; 0.6g of adipic acid dihydrazide; 1.5g of sodium dodecyl sulfate; 2.8g of OP-10; 25g of butyl acrylate; 20g of isooctyl acrylate; 2g of acrylic acid; 10g of isobutyl methacrylate; 0.03g of ethylene glycol dimethacrylate; 0.5g of ammonium persulfate; 45g of water; 0.5g of n-dodecyl mercaptan; 0.3g of sodium bicarbonate.
[0072] Example 4
[0073] Application of a water-based composite adhesive in the production of gold and silver cardboard:
[0074] S10, applying 5 g of water-based composite adhesive to one side of 1 square meter of aluminum-coated polypropylene film, laminating it with one side of 1 square meter of white cardboard, and performing hot roller lamination through a pressure roller through a 110° C. air duct for 10 seconds to obtain a composite material;
[0075] S20, hot pressing the other side of the aluminum-plated polypropylene film in the composite to form printing, so as to obtain gold and silver card paper, wherein the hot pressing temperature is 120° C. and the hot pressing time is 7 seconds.
[0076] Example 5
[0077] Application of a water-based composite adhesive in the production of gold and silver cardboard:
[0078] S10, applying 5 g of water-based composite adhesive to one side of 1 square meter of aluminum-coated polypropylene film, laminating it with one side of 1 square meter of white cardboard, and performing hot roller lamination through a pressure roller through a 110° C. air duct for 10 seconds to obtain a composite material;
[0079] S20, hot pressing the other side of the aluminum-plated polypropylene film in the composite to form printing, to obtain gold and silver card paper, wherein the hot pressing temperature is 110° C., and the hot pressing time is 5 seconds.
[0080] Example 6
[0081] Application of a water-based composite adhesive in the production of gold and silver cardboard:
[0082] S10, applying 5 g of water-based composite adhesive to one side of 1 square meter of aluminum-coated polypropylene film, laminating it with one side of 1 square meter of white cardboard, and performing hot roller lamination through a pressure roller through a 110° C. air duct for 10 seconds to obtain a composite material;
[0083] S20, hot pressing the other side of the aluminum-plated polypropylene film in the composite to form printing, so as to obtain gold and silver card paper, wherein the hot pressing temperature is 130° C. and the hot pressing time is 10 seconds.
[0084] Comparative Example 1
[0085] Compared with Example 1, Comparative Example 1 is the same as Example 1 except that diacetone acrylamide and adipic acid dihydrazide are not included.
[0086] Performance Testing
[0087] The appearance, solid content, viscosity, pH, glass transition temperature and glue strength of the water-based composite glue in Examples 1 to 3 and Comparative Example 1 were tested, wherein the solid content was tested by GB 1725-1979 "Determination of Solid Content of Coatings", the viscosity was tested by CB / T1723-93 "Determination of Coating Viscosity", the pH value was tested by a pH meter, the glass transition temperature was tested by GB / T37945-2019 "Test Method for Glass Transition Temperature of Materials for Organic Light Emitting Diode Displays - Differential Thermal Method", and the glue strength was tested by GB / T2423.3-2016 "Constant Wet Heat Test" method. The test results are shown in Table 1.
[0088] Table 1 Characterization of the water-based composite adhesive in Examples 1 to 3 and Comparative Example 1
[0089]
[0090]
[0091] The water-based composite adhesives in Examples 1 to 3 and Comparative Example 1 were used to prepare gold and silver cards using the methods of Examples 4 to 6, and the cards were observed to see whether wrinkles and bubbles occurred. The results are shown in Table 2.
[0092] Table 2 High temperature resistance of gold and silver cardboard prepared in Examples 1 to 3 and Comparative Example 1
[0093] Water-based composite adhesive Hot pressing method Wrinkling and blistering Example 1 Example 4 No wrinkles, no bubbles Example 2 Example 5 No wrinkles, no bubbles Example 3 Example 6 No wrinkles, no bubbles Comparative Example 1 Example 4 Wrinkles and bubbles
[0094] Figure 1 and Figure 2 The appearance of the gold and silver cards prepared by the water-based composite adhesive in Example 1 and Comparative Example 1 using the method of Example 4 are shown respectively. Figure 1 and Figure 2 It can be seen that the gold and silver cards prepared by the water-based composite adhesive of the present invention are not prone to wrinkling and bubbles under the hot pressing process.
[0095] The water-based composite adhesives in Examples 1 to 3 and Comparative Example 1 were used to prepare gold and silver cards using the methods of Examples 4 to 6, respectively, and placed at a constant temperature of 80° C. for 48 hours to check for wrinkling and blistering. The results are shown in Table 3.
[0096] Table 3 High temperature resistance of gold and silver cardboard prepared in Examples 1 to 3 and Comparative Example 1
[0097] Water-based composite adhesive Hot pressing method Wrinkling and blistering Example 1 Example 4 No wrinkles, no bubbles Example 2 Example 5 No wrinkles, no bubbles Example 3 Example 6 No wrinkles, no bubbles Comparative Example 1 Example 4 Wrinkles and bubbles
[0098] In summary, the gold and silver cardboard produced by the water-based composite adhesive provided by the present invention is hot pressed for 10 seconds at 110-130°C, and the composite paper does not show film-paper separation and blistering. After being placed at a constant temperature of 80°C for 48 hours, there is no wrinkle or blistering on the surface of the composite paper.
[0099] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A water-based composite adhesive, characterized in that: The raw material components include the following parts by weight: 0.5 to 1.2 parts of a first cross-linking monomer, wherein the first cross-linking monomer comprises an propylene compound having a ketocarbonyl group; 0.25 to 0.6 parts of a second crosslinking monomer, wherein the second crosslinking monomer comprises an alkyl compound having at least two hydrazide groups; 1.1 to 2.8 parts of surfactant; 30 to 45 parts of acrylic acid ester having a glass transition temperature of -70 to 60°C; 1-2 parts of acrylic acid; 5 to 10 parts of acrylic acid ester with a glass transition temperature of 106 to 158°C; 0.3-0.5 parts of initiator; 35-45 parts of water.
2. The water-based composite adhesive according to claim 1, characterized in that: The invention also comprises the following raw material components in parts by weight: 0.01 to 0.03 parts of acrylic acid alcohol ester.
3. The water-based composite adhesive according to claim 2, characterized in that: The acrylic alcohol ester includes at least one of ethylene glycol dimethacrylate, diethylene glycol diacrylate, and diethylene glycol dimethacrylate.
4. The water-based composite adhesive according to claim 1, characterized in that: The invention also comprises the following raw material components in parts by weight: 0.1 to 0.3 parts of a buffer; and 0.1 to 0.5 parts of a molecular weight regulator.
5. The water-based composite adhesive according to claim 1, characterized in that: The first cross-linking monomer includes diacetone acrylamide, ethyl acetoacetate methacrylate or N,N-methylenebisacrylamide; and / or, The second cross-linking monomer includes adipic acid dihydrazide, oxalic acid dihydrazide or succinic acid dihydrazide.
6. The water-based composite adhesive according to claim 1, characterized in that: The acrylic acid ester having a glass transition temperature of -70 to 60° C. includes at least one of ethyl acrylate, butyl acrylate and isooctyl acrylate; and / or, The acrylic acid ester having a glass transition temperature of 106 to 158° C. includes at least one of isobutyl methacrylate, isooctyl methacrylate or butyl methacrylate.
7. The water-based composite adhesive according to claim 1, characterized in that: The initiator comprises ammonium persulfate, potassium persulfate or sodium persulfate; and / or, The surfactant includes anionic surfactant and nonionic surfactant. The anionic surfactant includes sulfate, sulfonate or sodium sulfate of fatty alcohol ether. The nonionic surfactant includes ethanolamide, alkylphenol polyoxyethylene ether or fatty alcohol polyoxyethylene ether.
8. Use of the water-based composite adhesive as claimed in claim 1 in the production of gold and silver cardboard.
9. The use according to claim 8, characterized in that The following steps are involved: S10, applying water-based composite adhesive to one side of the laser film, laminating it with one side of the white cardboard or the powder-gray cardboard, and laminating them with a hot roller to obtain a composite material; S20, performing hot embossing on the other side of the laser film in the composite to obtain gold and silver card paper.
10. The use according to claim 9, characterized in that In step S10, the laser film includes an aluminized polypropylene film or an aluminized polyester film; and / or, In step S20, the temperature of the hot pressing is 110-130° C.; and / or, In step S20, the heat pressing time is 5 to 10 seconds.
Citation Information
Cited By
Water-based ink for flexographic printing and preparation method thereof
CN121271316A
A water-based ink for flexographic printing and a method for preparing the same
CN121271316B
